The Clinical Management of Traumatic Palatal Ulcers in an Adolescent Patient: A Common Lesion in Mini-Implant-Assisted Rapid Maxillary Expansion - Cristopher Barriga; Gonzalo Muñoz; Paulo Sandoval; Alejandro Lara; Flavio Copello (Medicina)
Background: This case report describes the clinical management of a traumatic palatal ulcer, a complication associated with mini-implant-assisted rapid maxillary expansion (MARPE). Case Report: A 13-year-old female patient with maxillary constriction underwent MARPE treatment using a custom acrylic expander anchored by four mini-implants. Despite proper planning and device design, the patient missed her first follow-up appointment and continued activations, resulting in tissue inflammation and embedding of the device. Upon examination, swelling and displacement of the cement were observed, necessitating device removal. The traumatic ulcer was treated with chlorhexidine gel, paracetamol, and a soft diet. Complete recovery was achieved within one month. A second expander was then designed and installed, with more frequent monitoring and improved hygiene protocols. This approach led to successful expansion without complications. This case highlights the importance of precise treatment planning, proper mini-implant selection, and regular follow-ups in MARPE therapy. It also emphasizes the need for patient compliance and effective hygiene measures to prevent complications. Conclusions: The successful management of the traumatic ulcer demonstrates that prompt action and consideration of cost-effective treatment options can lead to positive outcomes in addressing MARPE-related complications.